THE INTERACTION BETWEEN LANGUAGE AND SOCIAL ENVIRONMENT - Akmalkhonova S.; Aminova G. (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
Language is a system of signs (sounds, words, grammatical rules) used for communication, transmission of information, and expression of thoughts. The means of communication consist of a system of words and rules used by people or a group of people in one exact society, country, or continent; for example, Russian and English. This article explores the connection between the language and the social environment. This study delves into existing research papers and media analysis to compare language shifts and adaptations. This analysis opens up the idea that language is shaped by both the speaker and the receiver of the speech. It reveals that the media, globalization, and migration impact the emergence of hybrid language forms, like Spanglish and Singlish.